MANTENAN Application based on Android Sytem: Aplikasi MANTENAN berbasis Android - Fajar Suryansyah; Arif Senja Fitrani (Universitas Muhammadiyah Sidoarjo, 2021)
Marriage is one of God's commands that is highly recommended for its implementation. It's not just done, but how to make the marriage happen in the right time and quickly by hastening the marriage is expected to be one of the doors to the perfection of a servant of God. By making the MANTENAN application, it is expected to benefit both parties, where this application provides a place for service sellers. be it decoration services, building, catering, makeup, photographers, etc. And also to make it easier for buyers or prospective brides to choose or compare without the hassle of having to take time to come directly to the place. Only by opening the MANTENAN application, the buyer will be presented with various price options and also the quality of services provided by the seller.